About the models of supreme courts and the overruling of precedents - Delgado Suárez, Christian (2016)
The task of the Supreme Courts and the Constitutional Courts has undergone an evolution through years of history, from its classic reactive role to a more proactive one, which prevails in the current models.In this article, the author analyzes this evolution describing the roles -and their basis- of control of legality, as a classical function, and to give meaningto the normative text and complete the meaning of the legislative document with binding precedents, as a contemporary function. The author completesthe analysis focusing on the overruling and its application in Perú.